MSME Actors' perception on the implementation of digital tax in Indonesia - Loso judijanto; Nurul Hidayati Indra Ningsih; Rosma Ndiak; Fitriani Fitriani (Oikonomia : Journal of Management Economics and Accounting, 2024)
Digital tax has become an important issue in the era of technology-based economy, implemented in response to the increasing digital business activities, especially MSMEs. Although it aims to create a fair taxation system and increase state revenue, its implementation faces various challenges, especially related to business readiness and understanding. Many MSMEs still operate informally or semi-formally, so their understanding of digital tax is often limited. This phenomenon creates a significant information gap, especially in rural areas or for those who have just started digitalization. In addition, the diversity of perceptions towards this regulation affects the level of compliance, where some MSMEs find the policy burdensome, while others see it as a form of fairness and business professionalism. This study uses a descriptive qualitative approach to explore MSME players' perceptions of digital tax, with in-depth interviews and data analysis to understand the challenges and strategies adopted in dealing with the policy. The results are expected to provide strategic recommendations to improve the inclusiveness and effectiveness of digital tax implementation for MSMEs